Screening assessment of physical growth and development of rural children living near the Chornobyl zone (Environment & Health, 2016)
Objective. We studied assessment of the physical development of rural children living on radioactive contaminated as a result of the Chernobyl disaster in the regions of the Kiev region, using body mass indexes and Roerres.Materials and methods. A study was carried out of a children's population aged 6-17 years old living in Ivankivskyi and Polissya districts, directly adjoining the exclusion zone. The basis for study were anthropometric data obtained in the framework of in-depth survey of children and adolescent districts in 2014-2015. The analysis covered 1275 schoolchildren: 630 boys and 645 girls. As a screening test for assessing abnormalities in physical development, we used the body mass index and the Roerre index. The study of sexual-age characteristics of physical development was carried out by one-year age groups and enlarged: 6-9 years, 10-14 years old and 15-17 years. The standard of physical development of children was the normative values ​​of body mass indexes by sex and age, developed at the Institute of Hygiene and Medical Ecology named after A.N. Marzeev of the National Academy of Medical Sciences of Ukraine . Mathematical processing was performed using Microsoft Excel 2010 tables.Results It is shown that among the surveyed in all age groups, boys and girls with the magnitude of indices that are treated as a norm prevail. The frequency of dysharmonically developed children ranged from 32.0 to 41.0%, depending on gender and age, as well as the screening test that was used. Among disharmonious variants of physical development in schoolchildren of Ivano-Frankivsk and Polissya districts there were cases with excess body weight, especially in girls. Children of junior and senior school age are the most disadvantaged in physical development and require careful observation and adoption of corrective measures to prevent the development of diseases.
Keywords: physical growth and development; rural children; Chornobyl accident